“Colour Revolutions” and Russia - Valery Dmitrievich Solovey (Сравнительная политика)
The concept of "color revolutions" in the post-Soviet space remains popular among politicians and experts alike. However, Russia has not still developed a unified approach to the understanding of these processes. This article makes an attempt to analyze the triggers of the revolutions, as well as their results. The author also holds cross-temporal comparison, finding similarities in the policy of today’s Russia and the counter-revolutionary policy of Nicholas I in the XIX century. In addition, the author gives his assessment of the possibility of such a scenario in Russia.